READING FILMS AS HUMAN TEXTS: YESTERDAY AND THE DISMANTLING OF STIGMATISATION IN A PASTORAL HERMENEUTICS WITHIN THE CONTEXT OF THE HIV PANDEMIC - Louw, D. J. (Scriptura, 2009)
The paper, based on a masters’ thesis, explores the possibility of extending the traditional understanding of theology as fides quarens intellectum, with its emphasis on knowledge, to fides quares imaginem, with its emphasis on imagination. Therefore the important presupposition that, due to the aesthetic dimension of faith, care to people living with HIV should include the aesthetic dimension. If one links fides quares imaginem to fides quarens visum new options can be created for both theory formation and the practice of pastoral care in Practical Theology. In this regard the hypothesis is argued that the visual dimension of life as represented by media, and specifically film, should be utilised as part of HIV anti-stigma strategy, thus playing a role in a comprehensive HIV prevention strategy. The validity of this hypothesis is explored in an empirical study done with a group of farm workers and their families, and using the film Yesterday. It was done with this group as the need for stigmatisation intervention in lesser-educated, disadvantaged communities is fairly desperate.